Robotic surgery in pediatric urology - Adam Howe; Zachary Kozel; Lane Palmer (Asian Journal of Urology)
While robotic surgery has shown clear utility and advantages in the adult population, its role in pediatrics remains controversial. Pediatric-sized robotic instruments and equipment are not readily available yet, so certain modifications can be made in order to make robotic surgery successful in children. While the cost of robotic surgery remains high compared to open procedures, patients experience greater satisfaction and quality of life with robotic surgery. Robotic pyeloplasty is a standard of care in older children, and has even been performed in infants and re-do surgery. Other robotic procedures performed in children include heminephroureterectomy, ureteroureterostomy, ureteral reimplantation, urachal cyst excision, bladder diverticulectomy, and bladder reconstructive procedures such as augmentation, appendicovesicostomy, antegrade continence enema, bladder neck reconstruction and sling, as well as other procedures. Robotic surgery has also been used in oncologic cases such as partial nephrectomy and retroperitoneal lymph node dissection. Future improvements in technology with production of pediatric-sized robotic instruments, along with increases in robotic-trained pediatric urologists and surgeon experience along each's learning curve, will help to further advance the field of robotic surgery in pediatric urology.